Research progress on wireless sensor network (WSN) security technology. Issue 1 (1st April 2022) - Qichen, Wang
Abstract: Wireless sensor network (WSN) has been a frontier technology field that integrates a variety of technologies and has a wide range of applications in the military. Network security is of great significance in military warfare. First, this paper outlines the technical advantages of the application of military based on the technical characteristics of WSN. In military applications, WSN has been used in modern military combat while WSN features easy and fast deployment, high concealment, good fault tolerance, high accuracy and other obvious advantages. Moreover, from the perspective of network security, this paper reviews the research progress of network security technology at the network level and data level. The network level includes security protocols, key management, and secure routing technology, and key management includes pre-shared key mode and random key pre-distribution mode. At the data level, error control and fault-tolerant algorithms are mainly included. Automatic retransmission and forward error correction techniques are traditional error control methods, which should be combined with the specific situation of WSN to propose the corresponding fault-tolerant mechanism. Finally, this paper summarizes the practical applications of WSN in the military. From battlefield reconnaissance and target localization monitoring to destruction effect control and anti-terrorism equipment research, network security has been a top priority. Against the background of practical military applications, this paper summarizes the research significance of network security technology.